Resemblance as Evidence of Ancestry - Nelson, G. (Zootaxa, 2011)
The Connection between three ideas, resemblance as evidence of ancestry, was made long ago by Denis Diderot (1713–1784), a notable figure of the French enlightenment, the siècle des lumières (Lovejoy, 1904: 325). In 1753 he provided an example of what today is termed “transformational homology” (Patterson, 1982: 36): “If one considers the animal kingdom, and particularly the mammals, there is not one that lacks the functions and the parts, particularly internal ones, that are entirely similar to the others; so much so that it is easy to believe that there was a first prototype for all of them, for which nature merely elongated, shortened, transformed, multiplied, or obliterated certain organs. Imagine the fingers of the hand united, and the substance of the nails so abundant that it extends over the whole; then in place of the hand of a man, you have the foot of a horse.”